Dementia spousal caregivers and past transgressions: Measuring and understanding forgiveness experiences. (1st November 2016) - DeCaporale-Ryan, Lauren N.; Steffen, Ann M.; Marwit, Samuel J.; Meuser, Thomas M.
ABSTRACT: The transition from "wife" to "caregiver" for a cognitively impaired husband can be an overwhelming experience. Communication patterns change and small conflicts can grow, at times bringing angry feelings and new burdens. Engagement with forgiveness processes may benefit wives by lowering resentment over past tensions, restoring trust, and enhancing the overall caregiving experience. This study examined the utility of the Enright Forgiveness Inventory (EFI) within a sample of caregiving wives. Our intent was to better understand this population's experience with forgiveness when other contextual factors were likely to influence this process. Forgiveness scores on the EFI were positively related to the cognitive status of the care recipient, a particularly important finding for clinical intervention, and inversely related to marital distress and state anxiety.